Parental Perceptions About Alcohol Use for Their Adolescent with Attention-Deficit/Hyperactivity Disorder. Issue 5 (June 2020) - Harstad, Elizabeth; Sideridis, Georgios; Kaye, Dylan; Wisk, Lauren E.; Weitzman, Elissa R.; Levy, Sharon
ABSTRACT: Objective: Alcohol use can worsen attention-deficit/hyperactivity disorder (ADHD) symptoms, interfere with treatment, and worsen outcomes. Our objective was to describe parental perceptions of alcohol use for their adolescents with ADHD. Methods: Parents of adolescents with ADHD completed an online survey about perceptions of adolescent alcohol use for adolescents with ADHD. We described the level of parental concern about the impacts of alcohol use on their adolescent's functioning. We assessed whether specific covariates were associated with the level of parental concern. Results: Of 290 parents who completed the survey, 96.5% were women, and 66.1% had an educational attainment of college degree or higher. Most adolescents (75.4%) took ADHD medication, and 59.9% had comorbid anxiety or depression. Almost one-third (30.3%) of parents perceived that their adolescent was more likely to use alcohol because of ADHD, whereas 34.8% of parents disagreed with this and 34.8% of parents were neutral. Parents who suspected their adolescent regularly used alcohol were less likely to report concern about the impact of alcohol on their adolescent's school performance or ADHD medication effectiveness compared with parents who did not suspect regular adolescent alcohol use. Almost half of the parents (48.5%) did not report discussing the impact of alcohol use on ADHD with their adolescent. Conclusion: Many parents of adolescents with ADHD do not understand the unique risks of alcohol use for their adolescents. In addition, if alcohol use harm is not obvious, parents may not perceive there to be concerns about alcohol use on functioning. Parental education about alcohol use and ADHD is needed.